A porous activated carbon derived from banana peel by hydrothermal activation two-step methods - Hendronursito, Yusup; Astuti, Widi; Sabarman, Harsojo; Santoso, Iman (International Journal of Renewable Energy Development, 2025)
Activated carbon from banana peel waste through two stages of hydrothermal (HT) and physical activation processes has been carried out. The hydrothermal process was carried out at a temperature of 200 oC with a holding time of 2 or 6 hours. The hydrochar that had been obtained was then activated in the second stage with nitrogen gas flow (N2) at a temperature of 700 oC for 1 hour with a flow rate of 100 mL/min. The difference in treatment, without the HT process, two stages of activation, variations in activator agents (water, H3PO4, and PEG6000), water volume ratio and HT process holding time were studied for their effects on the specific surface area (SSA) and structure of activated carbon. SSA was measured using the Brunauer–Emmett–Teller (BET) adsorption method, x-ray crystallography was used to identify the crystalline phase and carbon structure parameters, and the surface morphology of activated carbon was observed using FESEM. The results showed that the activation method and process conditions greatly influenced the (SSA) of activated carbon. HT activation using a combination of activator agents produced an SSA reaching 476.9 m2/g. X-ray diffraction analysis showed that HT activation increased the degree of crystallization of activated carbon. The spherical surface structure of activated carbon was formed when H3PO4 was added, while the layered structure was formed when PEG6000 was used. Overall, the two-step activation preceded by the HT process with the addition of H3PO4 produced activated carbon with better SSA and carbon structure and has the potential to be used in wide applications such as EDLC supercapacitor electrode materials, battery cathodes, and adsorption materials.